Thiophene derivatives as corrosion inhibitors for 2024-T3 aluminum alloy in hydrochloric acid medium. Issue 17 (1st April 2022) - Arrousse, N.; Fernine, Y.; Al-Zaqri, Nabil; Boshaala, Ahmed; Ech-chihbi, E.; Salim, R.; El Hajjaji, F.; Alami, Anouar; Touhami, M. Ebn; Taleb, M.
Abstract : Thiophene derivatives: thiophene-2-carbaldehyde oxime (OXM) and 5-(thiophen-2-yl)-1 H -tetrazole (TET), were synthesized and characterized. Furthermore, their inhibitory property for AA2024-T3 in 1 M HCl solution was investigated via electrochemical and with theoretical study. Abstract : Thiophene derivatives, namely ( E )-thiophene-2-carbaldehyde oxime (OXM) and ( E )-5-(thiophen-2-yl)-1 H -tetrazole (TET), were synthesized and characterized via 1 H and 13 C NMR. Furthermore, their inhibitory property for AA2024-T3 in 1 M HCl solution was investigated via electrochemical impedance spectroscopy and potentiodynamic polarization at 293 K, together with DFT/B3LYP-based calculations. Numerous global and local descriptors of reactivity such as EHOMO, ELUMO, energy gap, electronegativity ( χ ), hardness ( η ), and frontier molecular orbital repartitions were investigated to describe the reactivity of each molecule. Alternatively, Monte Carlo simulations were performed under the solvation condition on the Al (111) surface to understand the adsorption behavior of the as-studied inhibitors deeply. The inhibition efficiency increased with an increase in the inhibitor concentration, achieving maximum values of 94.0% and 96% at 10 −3 M, respectively. The polarization curves showed that the examined compounds act as mixed-type inhibitors. In addition, the adsorption of these compounds obeyed the Al Awady, Flory-Huggins and Temkin isotherms. The surface characterization analysis via SEM/EDX confirmed the presence of a barrier layer covering the aluminum surface. The experimental inhibition efficiencies were correlated with global descriptors, which confirmed that this theoretical study is useful for the protection of aluminum alloy metal in an acidic medium.